PERAN NILAI KEARIFAN LOKAL PADA PENDIDIKAN 5.0 JENJANG PENDIDIKAN DASAR - Arlina Yuza; Hidayati Azkiya; Ade Sri Madona; Risa Yulisna; Dini Susanti (Universitas Negeri Medan, 2022)
The Role of Local Wisdom Values in Education 5.0 Elementary Education Level. Welcoming Society 5.0, Indonesia needs to prepare itself to be able to participate and be part of the world in the future. As an effort to deal with it, all elements of society need to improve themselves so that they can become superior Human Resources (HR). Educators as intermediaries for the formation of student character in schools have an important role to prepare students who are ready to compete in the next era. The research method used is a literature review. This study aims to review the role of local wisdom values in education 5.0 basic education level. The results of the study state that the affective abilities, psychomotor abilities, and cognitive abilities of students, especially at the education level if educators offer learning with local wisdom content, mobilize all creativity, innovate in the use of technology will help elementary school students to be ready to face 5.0 challenges and still have ancestral values. which builds the character of the nation's children who cannot be consumed by the negative effects of globalization.